Employee Multigeneraliy in the Aspect of the Use of ICT - Kocot, Maria (Multigeneracyjność pracownicza w aspekcie wykorzystania technologii ICT, 2022)
The aim of the article is to analyse the degree of use of ICT solutions by employees of Silesian companies from different generations. Research was conducted among 300 people from different generations and employed in Silesian enterprises. The conducted research has shown that representatives of the Baby Boomers generation have some difficulties in using ICT devices, and that their digital competences remain the lowest in relation to the younger generations. Yet, a small percentage of people from the oldest generation take part in training to increase their digital competences, and it would be a good practice to organise such training. It is very positive that the digital competences of the Y, X and Z generation employees are at a satisfactory level. The transfer of knowledge between generations could be a good solution members of younger generations could support older employees in the use of ICT.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 2 (64), s. 19-27
Keywords: ICT; multigenerationality; internet; enterprise; digital competences; technologie ICT; multigeneracyjność; przedsiębiorstwo; kompetencje cyfrowe